Analysis of Infection-Causing Factors and Antibiotic Sensitivity to the Degree of Ulcers in Diabetes Mellitus Patients - Ahmad Rizqi Ramadhan; Eva Niamuzisilawati; Tri Nugraha Susilawati; Dhani Redhono Harioputro (Jurnal Sehat Indonesia (JUSINDO), 2026)
The diabetic foot ulcer prevalence was 6.3% globally and 7.3% in Indonesia. This study analyzes the relationships between the type of germs and antimicrobial susceptibilities to the Wagner’s degree of diabetic-foot-ulcers on patients with type-2 diabetes mellitus admitted to Dr. Moewardi regional hospital. The method used in this observational analysis is a cross-sectional approach. The variables used were the type-of-germs, antimicrobial susceptibilities, and the degree of diabetic-foot-ulcers with the data extracted from 149 inpatients between the period of 2021-2022 and tested with Fisher’s-exact and multinomial-logistic-regressions. Data for the 4-most-frequent germs on the diabetic-foot-ulcers are Pseudomonas aeruginosa (17.4%; 26/149), Escherichia coli (12.8%; 19/149), Klebsiella pneumoniae ss. Pneumoniae (11.4%, 17/149) and Proteus mirabilis (10.7%; 16/149). Data for the 4-most-frequent antimicrobial susceptibilities are ampicillin (20,8%; 31/149), sulfamethoxazole (20,8%; 31/149), gentamicin (18,8%; 28/149) and amikacin (16,1%; 24/149). Data for the 3-most-frequent degree of diabetic-foot-ulcers are the 4th (39.6%; 59/149), 3rd (31.5%; 47/149) and 2nd (19.5%; 29/149) degrees. There is no relationship between the type-of-germs and the degree of diabetic-foot-ulcers (p=0.111). There is a relationship between antimicrobial susceptibilities and the degree of diabetic-foot-ulcers (p=0.009). There is a relationship between the type-of-germs and antimicrobial susceptibilities (p=0,0001). There is a simultaneous relationship between the type-of-germs (p=0.029) and antimicrobial susceptibilities (p=0.032) to the degree of diabetic-foot-ulcers (p=0.005). Therefore, it is necessary to conduct microbial culture and antimicrobial susceptibility tests on all patients with diabetic foot ulcers.